A New Era of Performance Evaluation. - Pieper, Sean M.; Paul, JoAnn M.; Schulte, Michael J. (Computer (00189162), 2007)
The article reports on the need for a revised framework for evaluating computer performance based on what the authors term "scenario-oriented computing." Traditionally, researchers have used latency and throughput as the primary performance measures, because until the turn of the millennium, computers generally executed one task at a time; there was a single input stream and a single output stream (I/O stream). Criteria are described for a revised metric suited to modern computer usage, which tends to involve "scenarios" of numerous I/O streams, timing information, and parallel tasks entering and leaving systems that increasingly run on multiple-core microprocessors, or multiprocessors.